Impaired Myocardial Oxygenation Response to Stress in Patients With Chronic Kidney Disease. Issue 8 (August 2015) - Parnham, Susie; Gleadle, Jonathan M.; Bangalore, Sripal; Grover, Suchi; Perry, Rebecca; Woodman, Richard J.; De Pasquale, Carmine G.; Selvanayagam, Joseph B.
Abstract : Background: Coronary artery disease and left ventricular hypertrophy are prevalent in the chronic kidney disease (CKD) and renal transplant (RT) population. Advances in cardiovascular magnetic resonance (CMR) with blood oxygen level–dependent (BOLD) technique provides capability to assess myocardial oxygenation as a measure of ischemia. We hypothesized that the myocardial oxygenation response to stress would be impaired in CKD and RT patients. Methods and Results: Fifty‐three subjects (23 subjects with CKD, 10 RT recipients, 10 hypertensive (HT) controls, and 10 normal controls without known coronary artery disease) underwent CMR scanning. All groups had cine and BOLD CMR at 3 T. The RT and HT groups also had late gadolinium CMR to assess infarction/replacement fibrosis. The CKD group underwent 2‐dimensional echocardiography strain to assess fibrosis. Myocardial oxygenation was measured at rest and under stress with adenosine (140 μg/kg per minute) using BOLD signal intensity. A total of 2898 myocardial segments (1200 segments in CKD patients, 552 segments in RT, 480 segments in HT, and 666 segments in normal controls) were compared using linear mixed modeling. Diabetes mellitus ( P =0.47) and hypertension ( P =0.57) were similar between CKD, RT, and HT groups. The mean BOLD signal intensity change was significantly lower in the CKD and RT groups compared to HT controls and normal controls (−0.89±10.63% in CKD versus 5.66±7.87% in RT versus 15.54±9.58% in HT controls versus 16.19±11.11% in normal controls, P <0.0001). BOLD signal intensity change was associated with estimated glomerular filtration rate (β=0.16, 95% CI=0.10 to 0.22, P <0.0001). Left ventricular mass index and left ventricular septal wall diameter were similar between the CKD predialysis, RT, and HT groups. None of the CKD patients had impaired global longitudinal strain and none of the RT group had late gadolinium hyperenhancement. Conclusions: Myocardial oxygenation response to stress is impaired in CKD patients and RT recipients without known coronary artery disease, and unlikely to be solely accounted for by the presence of diabetes mellitus, left ventricular hypertrophy, or myocardial scarring. The impaired myocardial oxygenation in CKD patients may be associated with declining renal function. Noncontrast BOLD CMR is a promising tool for detecting myocardial ischemia in the CKD population.